Psychesync: Smartwatch tracking and classifying mental health for personalized wellbeing / Nurhasniza Idham Abu Hasan ... [et al.] - Abu Hasan, Nurhasniza Idham; Ganggayah, Mogana Darshini; Jamal, Nur Faezah; Abu Hasan, Nurhasnira (2024)
Long-term and persistent mental health problems can lead to severe mental disorders and even death in individuals. The real-time and accurate classification of individual mental health has become an effective method to prevent the occurrence of mental health disorders. In recent years, intelligent wearable devices have been widely used for monitoring mental health and have played a significant role. This study aims to devise an innovative design approach for smartwatch prototypes that can accurately classify individual mental health conditions. The aspiration is for this smartwatch to facilitate early detection, prevention, and intervention, thereby serving as a blueprint for enhancing individual mental well-being.